PENGARUH MEDIA KOMIK CERITA ANAK TERHADAP KEMAMPUAN MENULIS TEKS NARASI SISWA KELAS V SDN 1 KEDIRI SELATAN TAHUN PELAJARAN 2020/2021 - Hendri, Muhammad; Tahir, Muhammad; Setiawan, Heri (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The problem raised in this study is the influence of children's story comics media on the ability to write narrative texts for fifth grade students at SDN 1 Kediri Selatan in the 2020/2021 school year. The aim is to determine the effect of children's story comics media on the ability to write narrative texts for fifth grade students at SDN 1 Kediri Selatan in the 2020/2021 school year. The results of this study are expected to be useful theoretically and practically. The concept used in this research is the media of children's story comics and writing skills. This type of research is a quantitative descriptive study, the data sampling technique is the Simple Random Sampling technique (aims to take several samples from several populations). The data collection technique used a written test. Hypothesis testing was carried out using the T test with the help of SPSS version 25. The results showed that the lowest value of the experimental pretest was 37 while the highest was 54 and the lowest was for the control class 39 and the highest was 48, then for the experimental posttest, the lowest value was 76 and the highest score was 85. , for the posttest control class the lowest score is 80 and the highest is 92. This shows that there is an influence of children's story comics media on the ability to write narrative texts for the fifth grade students of SDN 1 Kediri Selatan in the 2020/2021 school year.